Impact of the COVID-19 vaccination on confusion around vaccination in general: A longitudinal study on a university population over 18 months. - Marine Paridans; Justine Monseur; Nicolas Gillain; Eddy Husson; Gilles Darcis; Claude Saegerman; Laurent Gillet; Fabrice Bureau; Anne-Françoise Donneau; Michèle Guillaume; Benoit Pétré (PLOS Global Public Health)
Even before the COVID-19 pandemic, vaccine hesitancy was one of the main global public health threats. Unfortunately, the COVID-19 crisis and its associated risks only reinforced this hesitancy. This study aimed to identify to what extent the COVID-19 vaccination affected confusion around vaccination in general, its change and any associated factors. A questionnaire was distributed to the university population of Liège between April-June 2021 (Time 1) and July-September 2022 (Time 2). The impact of the COVID-19 vaccination on confusion around vaccination in general (score 0 to 100) was divided into three groups based on the tertiles of the study sample at different times and whether or not any change had been observed. Ordinal and multinomial regression analyses were performed to assess the relationship between the confusion and various determinants. The sample consisted of 491 participants. Time 1 vs Time 2, 41.3% vs 35.4% seemed to be less confused, 24.2% vs 28.7% were moderately confused and 34.4% vs 35.8% more confused, respectively. In terms of change, 19.4% of participants were less confused, 55.2% had not changed their opinion and 25.5% were more confused. The determinants causing confusion at both times and regarding change were self-perception, health literacy, past vaccination experiences and COVID-19 related factors (COVID-19 vaccination intention and trust in source of information at Time 1; preferred source of information, trust in vaccine producers and conspiratorial beliefs at Time 2; trust in vaccine producers for change). The results demonstrated that the COVID-19 vaccination impacted confusion around vaccination in general. Both unrelated and related COVID-19 factors, particularly regarding the progression of the pandemic, seem to have contributed to this confusion. Contributing factors require a personalised approach, evidence-based information being communicated with messages adapted to the situation and its evolution designed to allay individuals' fears about vaccination.